2007
DOI: 10.1118/1.2745923
|View full text |Cite
|
Sign up to set email alerts
|

Impact of inhomogeneity corrections on dose coverage in the treatment of lung cancer using stereotactic body radiation therapy

Abstract: The purpose of this study is to assess the real target dose coverage when radiation treatments were delivered to lung cancer patients based on treatment planning according to the RTOG-0236 Protocol. We compare calculated dosimetric results between the more accurate anisotropic analytical algorithm (AAA) and the pencil beam algorithm for stereotactic body radiation therapy treatment planning in lung cancer. Ten patients with non-small cell lung cancer were given 60 Gy in three fractions using 6 and 10 MV beams … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
65
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 55 publications
3
65
0
Order By: Relevance
“…Ding et al [14] found that the AAA calculations at 6 MV agreed very well with their measurements, whereas the calculations at high energy overestimated the dose delivered to the lung. They also found that PBC overestimated the dose in the lungs with up to 12Á25%.…”
Section: Discussionmentioning
confidence: 86%
“…Ding et al [14] found that the AAA calculations at 6 MV agreed very well with their measurements, whereas the calculations at high energy overestimated the dose delivered to the lung. They also found that PBC overestimated the dose in the lungs with up to 12Á25%.…”
Section: Discussionmentioning
confidence: 86%
“…Bush et al (10) reported that AAA underestimated BEAM/DOSXYZnrc by 8% within lung (0.24 g cm1) using 18 MV 4×4 cm2 beam incident on water‐lung‐water phantom. Ding et al (25) reported a 6.0% difference between MC and AAA in lung using a 3×3 cm2, 10 MV single beam. The variations in differences between our findings and the aforementioned studies originate from the different lung density (0.3 g/cm3), phantom structure, and beam configuration used in our study.…”
Section: Discussionmentioning
confidence: 99%
“…( 33 ) The AAA algorithm makes use of precalculated Monte Carlo dose kernels and provides better dose modeling than the pencil beam algorithm, especially for heterogeneous media. ( 34 ) However, in the open‐field validation, we found that the 15 cm hollow structure in the ArcCHECK system indeed leads to an overestimation in the TPS dose calculation (Fig.…”
Section: Discussionmentioning
confidence: 99%